Agriculture creates subtle genetic structure among migratory and nonmigratory populations of burrowing owls throughout North America. Issue 19 (17th September 2020) - Macías‐Duarte, Alberto; Conway, Courtney J.; Culver, Melanie
Abstract: Population structure across a species distribution primarily reflects historical, ecological, and evolutionary processes. However, large‐scale contemporaneous changes in land use have the potential to create changes in habitat quality and thereby cause changes in gene flow, population structure, and distributions. As such, land‐use changes in one portion of a species range may explain declines in other portions of their range. For example, many burrowing owl populations have declined or become extirpated near the northern edge of the species' breeding distribution during the second half of the 20th century. In the same period, large extensions of thornscrub were converted to irrigated agriculture in northwestern Mexico. These irrigated areas may now support the highest densities of burrowing owls in North America. We tested the hypothesis that burrowing owls that colonized this recently created owl habitat in northwestern Mexico originated from declining migratory populations from the northern portion of the species' range (migration‐driven breeding dispersal whereby long‐distance migrants from Canada and the United States became year‐round residents in the newly created irrigated agriculture areas in Mexico). We used 10 novel microsatellite markers to genotype 1, 560 owls from 36 study locations in Canada, Mexico, and the United States. We found that burrowing owl populations are practically panmictic throughout the entire North American breeding range. However, an analysis of molecular variance provided some evidence that burrowing owl populations in northwestern Mexico and Canada together are more genetically differentiated from the rest of the populations in the breeding range, lending some support to our migration‐driven breeding dispersal hypothesis. We found evidence of subtle genetic differentiation associated with irrigated agricultural areas in southern Sonora and Sinaloa in northwestern Mexico. Our results suggest that land use can produce location‐specific population dynamics leading to subtle genetic structure even in the absence of dispersal barriers. Abstract : Migration‐driven breeding dispersal in the burrowing owl, whereby long‐distance migrants from Canada and the United States became year‐round residents in the newly created irrigated agriculture areas in northwestern Mexico, may explain the species' population decline in northern latitudes. In support of this hypothesis, (a) owl populations in northwestern Mexico and Canada together are more genetically differentiated from the rest of the populations, and (b) there is a subtle genetic differentiation associated with irrigated agricultural areas in northwestern Mexico.